Research in the social scientific study of religion. - Village, Andrew.; Hood, Ralph W., Jr., 1942- (Research in the Social Scientific Study of Religion, 2015)
This volume includes a wide range of papers that explore individual and institutional aspects of religion from a social-science perspective. The special section has articles from research groups in Europe, the USA and Australia on clergy work-related psychological health, stress, burnout and coping strategies. The general papers include studies on coping strategies among Buddhists, gender differences in response to church decline, teenage participation in religion, social capital among Friends of Cathedrals, psychological profiles of clergy, education effects on Roman Catholic deacons, and an analysis of prayer requests. Together these papers form a valuable collection indicating the depth and vibrancy of research in these fields.